Pharmacokinetics and Pharmacogenetics of Dabigatran - A. V. Savinova; V. S. Dobrodeeva; M. M. Petrova; R. F. Nasyrova; N. A. Shnayder (Рациональная фармакотерапия в кардиологии, 2021)
Dabigatran etexilate is a prodrug of dabigatran, a oral direct inhibitor of thrombin. Pharmacokinetics of dabigatran etexilate doesn’t have the disadvantages of vitamin K antagonists. However, pharmacokinetics and pharmacogenetics of dabigatran are variable. This can affect both effectiveness and safety of anticoagulant therapy. It is considered that CES1 enzyme and P-glycoprotein (CES1 and ABCB1 genes accordingly) play important role in pharmacokinetics of dabigatran etexilate. UDP-glucuronosyltransferase enzymes UGT2B15, UGT1A9, UGT2B7 (UGT2B15, UGT1A9, UGT2B7 genes accordingly) take part in the metabolism of active dabigatran. Presence of these gene’s single-nucleotide variants (SNV) can affect effectiveness and safety of dabigatran etexilate usage. The goal of this review is analysis of associated researches of SNV genes CES1 and ABCB1 and search for new candidate genes that reveal effectiveness and safety of dabigatran etexilate usage.Materials and methods. The search for full-text publications in Russian and English languages containing key words “dabigatran etexilate”, “dabigatran”, “pharmacokinetics”, “effectiveness”, “safety” was carried out amongst literature of the past twenty years with the use of eLibrary, PubMed, Web of Science, OMIM data bases. Pharmacokinetics and pharmacogenetics of dabigatran etexilate are considered in this review. The hypothesis about UDP-glucuronosyltransferase enzymes influence on dabigatran metabolism was examined. Nowadays more than 2000 SNV CES1 and ABCB1 genes are identified, but their potential influence on pharmacokinetics of dabigatran etexilate and its active metabolite (dabigatran) in clinical practice needs to be further researched. Role of SNV UDP-glucuronosyltransferase genes (UGT2B15, UGT1A9, UGT2B7) in dabigatran’s effectiveness and safety is not explored enough. However, UGT2B15 gene can be a potential candidate gene for research on safety of this drug.